Innovation of Aceh songket motifs with the 'tsunami' theme as a disaster education media in the community [Inovasi motif songket aceh dengan tema tsunami sebagai media edukasi kebencanaan di masyarakat] - Arafat, Pratitou; Silvalila, Meilya; Zahrah, Aghnia; Nabila, Amira Qisthy (Buletin Pengabdian, 2025)
One of the efforts to reduce disaster risk is through sustainable and long-lasting disaster knowledge transmission. A cultural approach can serve as an effective method to convey disaster-related knowledge across generations. One form of cultural product considered suitable as a medium for delivering tsunami disaster messages in Aceh is the Aceh Songket textile, which has coexisted with the Acehnese community for centuries. This community service aims to create a new design motif for Aceh Songket that carries a reminder message about the 2004 Indian Ocean Tsunami disaster. The activity was conducted in collaboration with an Aceh Songket weaving group, involving the process of motif design and prototype creation. A rational design method was employed, using structured, detailed, and clear steps to achieve an optimal design solution. The outcome of this service is a motif entitled Tsunami, which is expected to be produced by Songket artisans and widely disseminated within the community, thereby serving effectively as a medium for long-term and intergenerational disaster risk awareness and knowledge regarding the Aceh Tsunami. In conclusion, the Aceh Songket motif with the Tsunami theme as a disaster education medium in the community has been successfully developed, with the main product being a tsunami-themed motif for Aceh Songket weaving. This design is anticipated to be broadly adopted by Acehnese weavers as an alternative for new motif development, which has been rarely explored previously.